Impact of chronic kidney disease on health-related quality of life in the pediatric population: meta-analysis (2020)
Objective: To meta-analyze health-related quality of life in pediatric patients with chronic kidney disease in comparison to healthy patients according to the dimensions of the PedsQL instrument. Sources of data: A systematic review was performed with meta-analysis for the mean difference in each of the health-related quality of life dimensions. The authors searched for ten scientific databases including PubMed, Scopus, SciELO, Science Direct, ProQuest, Google Scholar. Reproducibility by the Kappa index was evaluated, and Dersimonian and Laird's tests, RI coefficient, Begg statistic, Forest Plot, and sensitivity analysis were carried out. Summary of the findings: 17 investigations were included in the qualitative synthesis and 7 in the quantitative synthesis with a population of 1214 of both healthy and sick pediatric patients with 3-5 chronic kidney disease stages. The health-related quality of life in pediatric chronic kidney disease patients presented lower scores in all the evaluated dimensions: in the physical dimension the difference is of 13.6 points, in the emotional dimension 7.8, in the social dimension 8.2, in the school dimension 20.8, with the total difference being 17.7 points. Conclusion: The findings of this study show that pediatric patients have lower health-related quality of life in all the evaluated dimensions, with the "school" dimension being the most affected and the "emotional" one the least. In this sense, we suggest monitoring the health-related quality of life of pediatric patients with chronic kidney disease so that interventions can be oriented to strengthen the affected dimensions, including adjustments to daily life and prevention of complications related to the disease.